Enhancing Mathematical Interest and Learning Outcomes: The Lift-the-flap Book Incorporating Tolaki Local Wisdom and Islamic Values - Samrin, Samrin; Riansyah, Firman; Patih, Tandri; Tarty, Indri Purnama; Nastiti, Dyah Kumala (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research addresses the problem of low student interest and learning outcomes in junior high school mathematics. It aims to develop a lift-the-flap mathematics book contextualized with Tolaki local wisdom and Islamic religious values and investigate its impact on students' interest and achievement. The study was conducted following the Research and Development (R&D) framework, specifically the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation phases for instructional design. The teaching material developed was applied to a Grade VII Junior High School class focusing on numerical topics. Results from data analysis suggested that the material demonstrated a good level of feasibility, scoring 76 percent for media feasibility and 77 percent for content feasibility. Overall, the material was well received by both teachers and students, with positive response rates of 74 percent and 85 percent, respectively. Descriptive analysis indicated a notable increase of 26.43 percent in students' interest in learning mathematics following the use of the lift-the-flap book. Moreover, inferential statistics revealed a significant improvement in students' interest and learning outcomes in mathematics after the implementation of the teaching materials contextualized with Tolaki local wisdom and Islamic religious values. The improvement was statistically significant with a p-value less than 0.05, indicating that the lift-the-flap book has substantial potential in enhancing mathematics education. Based on the results, we recommend further studies to investigate the impact of such culturally-infused teaching materials on other aspects of learning, and exploration of its applicability in other educational levels or subjects.